2019
DOI: 10.14444/6060
|View full text |Cite
|
Sign up to set email alerts
|

Initial Single-Institution Experience With a Novel Robotic-Navigation System for Thoracolumbar Pedicle Screw and Pelvic Screw Placement With 643 Screws

Abstract: Background: Robotic-guided navigation systems for pedicle screw placement has gained recent interest to ensure accuracy and safety and diminish radiation exposure. There have been no published studies using a new combined robotics and navigation system (Globus ExcelsiusGPS system). The purpose of this study was to demonstrate safety with this system. Methods: This is a case series of consecutive patients at a single institution from February 1, 2018, to August 31, 2018. All patients who had planned placement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Jain et al reported no screw related complications or returns to the operating room with 643 screws placed. Of the 66 screws that were reviewed with post-operative CT scanning, 100% of those were categorized as GR A or B (40). In their series of 600 screws all reviewed with post-operative CT, Wallace et al reported a GR A or B grade for 98.2% of the screws.…”
Section: Pedicle Screw Accuracy In Current Platformsmentioning
confidence: 99%
“…Jain et al reported no screw related complications or returns to the operating room with 643 screws placed. Of the 66 screws that were reviewed with post-operative CT scanning, 100% of those were categorized as GR A or B (40). In their series of 600 screws all reviewed with post-operative CT, Wallace et al reported a GR A or B grade for 98.2% of the screws.…”
Section: Pedicle Screw Accuracy In Current Platformsmentioning
confidence: 99%
“…Intraoperatively, AP and lateral fluoroscopic images of the levels to be instrumented are obtained. Fluoroscopic images and the preoperative CT scan are then merged, and the surgeon verifies the reconstruction based on planned screw trajectories from fluoroscopic images and CT scans [6]. The robot is then draped sterilely, locked into place, and the robotic arm aligns the end effector to the planned trajectory; the desired screw label is selected.…”
Section: Preoperative Ct With Intraoperative Fluoroscopymentioning
confidence: 99%
“…The robot is then draped sterilely, locked into place, and the robotic arm aligns the end effector to the planned trajectory; the desired screw label is selected. The screw hole is drilled and tapped, and the screw is then placed [6].…”
Section: Preoperative Ct With Intraoperative Fluoroscopymentioning
confidence: 99%
“…30 Like their role in pedicle screw accuracy, robotics and navigation have been implemented to improve the accuracy of S2-AI screw placement with published accuracy rates between 96% and 100%. [31][32][33] Furthermore, because direct visualization is not necessary, robotic-assisted S2-AI screws are ideal for sacropelvic fixation by a percutaneous technique for minimally invasive (MIS) deformity cases.…”
Section: Sacropelvic Fixationmentioning
confidence: 99%
“…Single-position lateral surgery has been shown to be an efficient method for thoracolumbar deformity correction while limiting operative and anesthetic time. 33 This method can be effective in patients who would benefit from anterior or lateral interbody device placement in addition to pedicle screw fixation. The main limitation of single-position lateral surgery is the increased difficulty in performing significant complex posterior work.…”
Section: Single Position Lateralmentioning
confidence: 99%